Biomechanics in table tennis - Malagoli Lanzoni, I. (ITTF Webinar, 9st September 2020, 2020)
As part of our webinar series "Table Tennis at your Fingertips", Ivan Malagoli Lanzoni, adjunct professor for theory and methodology of training at Bologna University spoke to us about "Biomechanics in Table Tennis". 1.General definitions 2.Revisionof the TT literature: methods 3.TT Examples 4.TT Examples: News 5.Conclusions